Development of Smart Apps Creator-Based Learning Media for the Human Auditory System Topic in IPAS Subject for Grade V at SDN 14 Ampenan - Fitri Cahyani; Muhammad Erfan; Prayogi Dwina Angga (Journal of General Education and Humanities, 2025)
Learning media play a crucial role in the success of the educational process. Without appropriate media, learning tends to become monotonous, relying solely on the teacher and lacking variety in resources. The integration of media significantly influences students' cognitive development. Observations and questionnaire distribution revealed learning challenges, where teachers predominantly used LKS (student worksheets), resulting in low student achievement in the topic of the human auditory system. Conversely, the potential analysis showed that all students owned smartphones. This research aimed to develop a valid and practical learning medium on the topic of the human auditory system using Smart Apps Creator. This study employed a Research and Development (R&D) design using the Sugiyono model to evaluate the feasibility and practicality of the developed media. The study was conducted at SDN 14 Ampenan, involving 19 fifth-grade students. Instruments included validation questionnaires for material experts and media experts, as well as practicality questionnaires for student and teacher responses. The results showed: (1) material expert validation yielded a score of 83.3%, indicating a "very valid" qualification; (2) media expert validation reached 76.6%, indicating a "valid" qualification; (3) product trials by teachers and students resulted in scores of 87.64% and 87.5% respectively, classified as "very practical"; and (4) implementation trials scored 93.05% (teacher) and 95.2% (student), also categorised as "very practical." Based on these findings, the Smart Apps Creator-based learning media is considered feasible and effective for use in the classroom. The media is designed to be interactive, enabling students to actively engage in the learning process through features such as simulations, quizzes, and real-time feedback, thereby enhancing their understanding of the material.